Infraestructura 5G Standalone para Investigación y Desarrollo - Tarrías Muñoz, Antonio; Baena-Martínez, Eduardo; Fortes-Rodríguez, Sergio; Barco-Moreno, Raquel (My University, 2022)
The deployment of 5G infrastructures has been notably addressed during the last years. In contrast, most of the cellular operators are opting for deploying 5G Non- Standalone (NSA), which relies on LTE as anchor technology (signaling, guaranteed coverage...). Nevertheless, 5G NSA is not able to provide all the enhancements that 5G envisions to introduce, including a wide variety of services and use cases. At the University of Ma ́laga, a complete 5G Standanlone (SA) private network has been deployed for research and development purposes. This infrastructure is composed by both indoor and outdoor cells with different equipment, respectively. It enables the use novel technologies such as beamforming to achieve better capacity and coverage, which means higher bandwidths and lower latencies. The aim of this work is to analyze the benefits in terms of transmission bandwidth and latency with reference to a LTE private network. To accomplish this, some tests have been performed over the 5G SA network, providing also some insights about the use of MEC (Multi-access Edge Computing) in 5G.
Keywords: Redes de banda ancha - Congresos; 5G; Standalone; Infraestructura